SNP discovery of Korean short day onion inbred lines using double digest restriction site-associated DNA sequencing - Lee, Ji-Hee (PLoS One, 2018)
Onion (Allium cepa L.) is an economically important vegetable crop around the world. Genetic and genomic research into various onion accessions will provide insights into the onion genome to enhance breeding strategies and improve crops. However, the onion’s large genome size means that studies of molecular markers are limited in onion. This study aimed to discover high quality single nucleotide polymorphisms (SNPs) from 192 onion inbred lines relating to short-day cultivation in Korea. Paired-end (PE) double digested restriction site-associated DNA sequencing (ddRAD-seq) was used to discover SNPs in onion. A total of 538,973,706 reads (25.9 GB), with an average of 2,658,491 high-quality reads, were generated using ddRAD-seq. With stringent filtering, 1904 SNPs were discovered based on onion reference scaffolds. Further, population structure and genetic relationship studies suggested that two well-differentiated sub-populations exist in onion lines. SNP-associated flanking sequences were also compared with a public non-redundant database for gene ontology and pathway analysis. To our knowledge, this is the first report to identify high-quality SNPs in onion based on reference sequences using the ddRAD-seq platform. The SNP markers identified will be useful for breeders and the research community to deepen their understanding, enhance breeding programs, and support the management of onion genomic resources.